2021
DOI: 10.1177/2050313x211039377
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute COVID-19 functional movement disorder

Abstract: Movement disorders are rare compared to other neurological manifestations of COVID-19. Patients who have recovered from acute severe acute respiratory syndrome coronavirus-2 infection continue to have multiple debilitating symptoms months later. We report a case of 54-year-old man who presented with repetitive flexion movement of head which started 2 months after severe acute respiratory syndrome coronavirus-2 infection. Extensive work-up including neurological examination, neuroimaging, cerebrospinal fluid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…These cognitive symptoms were associated with the presence of hypometabolic clusters in the brains of patients with PACS, as demonstrated using fluorodeoxyglucose (FDG)-positron emission tomography (PET) 30 . In addition, a recent case report described a patient that presented with a movement disorder after COVID-19 infection 14 . Previous studies showed a surge in tics and tic-like attacks during the COVID-19 pandemic, suggesting that this surge was due to the stress induced by the pandemic 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cognitive symptoms were associated with the presence of hypometabolic clusters in the brains of patients with PACS, as demonstrated using fluorodeoxyglucose (FDG)-positron emission tomography (PET) 30 . In addition, a recent case report described a patient that presented with a movement disorder after COVID-19 infection 14 . Previous studies showed a surge in tics and tic-like attacks during the COVID-19 pandemic, suggesting that this surge was due to the stress induced by the pandemic 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies performed regarding PACS indicated that COVID-19 survivors might suffer from long-term debilitating symptoms after their recovery 12 . Although several studies have characterized these symptoms, most of them were performed on hospitalized COVID-19 patients, and new symptoms are still being reported, such as movement disorders 14 . In addition, the duration of time that should elapse for these symptoms to subside has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This study further unveiled alterations of multiple common factors involved in cognitive impairment observed in COVID-19 and AD. There is evidence that SARS-CoV-2 can aggravate the clinical presentations of PD [ 173 , 174 , 175 , 176 ] and cause de novo problems with gait, movement, coordination, and balance [ 177 , 178 , 179 , 180 ]. The lasting impacts of SARS-CoV-2 infection on microglial plasticity and its contribution to the pathophysiology of post-COVID-19 neurological sequelae and disorders, including PD, were comprehensively discussed in a recent review [ 181 ].…”
Section: Covid-19 and Neurodegenerationmentioning
confidence: 99%
“…Frequently, fatigue and anxiety are also part of the disease spectrum [ 17 ]. Various authors reported an increase in the incidence of FMD during the COVID-19 pandemic, possibly in relation to a higher level of stress [ 18 , 19 ]. Hull et al reported an increase of 60% in the number of patients diagnosed with FMD during the pandemic [ 18 ].…”
Section: Neurological Impairment In Covid-19mentioning
confidence: 99%